Incidence and Management of In-Stent Restenosis in Patients with Drug-Eluting Stents - Farooq, Muhammad; Naeem, Muhammad; Ashraf, Muhammad Waseem; Aslam, Muhammad; Saqi, Muhammad Attiq Ur Rehman; Abubakar, Muhammad (Indus Journal of Bioscience Research, 2024)
Introduction: The most prevalent complication of cardiac intervention is restenosis. After the BMS period, drug-eluting stents (DES) are the most suitable choice for stenosis treatment, particularly for patients with a high risk of bleeding. The rate of restenosis was much lower with current DES technology. The introduction of drug-eluting balloons (DEBs) is a potential breakthrough for coronary revascularisation treatments, particularly in-stent restenosis. Objective: This retrospective study was carried out to find the incidence and management of in-stent restenosis in patients with drug-eluting strains. Methods: After the hospital ethics committee’s permission, patients’ medical data was evaluated. Clinical and personal data were acquired from medical records. Risk variables for atherosclerosis were collected, along with baseline labs and echocardiography, to assess the ejection fraction of each patient. Classified interventional cardiologists analysed angiographic pictures to confirm the existence of ISR. Details about prior angioplasty and the kind of stent were noted. All patients with considerable drug-eluting in-stent restenosis (DES-ISR) and eligible for therapy with DEB were included in the analysis. Results: Two hundred ninety-eight patients received at least one DES throughout the research period. ISR was identified in 50 individuals (16.77%). Thus, 50 patients who fulfilled the inclusion criteria were included in the study. 2% of the study population presented with STEMI, 22% with NSTEMI, 24% with UA, and 52% presented with non-ACS. Among all the patients that had ISR, diabetes and hypertension were the most common comorbidities found in the study population. Following coronary angiography, it was discovered that the frequency of ISR was 11(22%) in patients with Xlimus sirolimus stent, 10(20%) with Xience (everolimus-eluting stent), 13(26%) with Ultimate (sirolimus-eluting stent), and 16(32%) with Biomatrix stent. Twenty-eight patients with DES ISR who met the inclusion criteria received revascularisation with DEB. After a median of 18 months of follow-up, eight patients remained symptomatic, with 4 developing MACE, one resulting in cardiac death, and 3 requiring revascularisation. Thus, the overall MACE rate was 21%. There were two fatalities from non-cardiac causes. Conclusions: In all new-generation DES, ISR often manifests as angina. There was no statistically significant difference in terms of ISR between second- and third-generation DES.DEB technology, particularly for DES, holds potential for ISR. Our experience highlights the need for more data, including randomised studies in various patient groups.